A Comparative Study on Professional and Non Professional Women Volleyball Players on Selected Anthropometric Variables: A Comparative Study on the Impact of Professionalism on Anthropometric Variables in Women Volleyball Players (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Volleyball is a complex game of simple skills. It has also shown in recent years that there is atrend that volleyball payers adopt the technique, tactics and physical performance. Volleyball Gamerequires comprehensive ability including physical, technical, mental and tactical abilities. Among themphysical abilities of players exert marked effects on the skills of the players themselves and the tacticsof the team. In order to succeed at the highest level in volleyball, a team sport, players must possesscertain anthropometric traits, especially when it comes to domination over the net. While team courtsports have been widely researched, no studies have been conducted comparing data from professional non professional women volleyball players. Moreover, the differences in biomotor abilities,physiological and anthropometric them are also unknown. The present extensive study may elucidatewhich bio motor ability, physiological and anthropometric characteristics are most impacted byparticipation in Volleyball as professional and non professional players. For comparison betweenprofessional non-professional women volleyball players, the investigator chose speed, strength,flexibility, agility from the many biomotor skills from the many physiological factors, resting pulserate, VO2 max, mean arterial blood pressure, breath holding time and from the many anthropometricfactors, standing height, weight, arm length, leg length.